Hybrid project-based learning for problem-solving skils and student creativity in plant anatomy and physiology courses - Ilma, Silfia; Adhani, Aidil; Sarira, Nelsiani Thomas (Universitas Negeri Jakarta, 2023)
Problem solving and creativity skills are very important skills for students to face global challenges. This study aims to analyze the effect of the Hybrid project-based learning (HPBL) learning model on students' problem-solving skills and creativity. This research used a pretest-posttest non-equivalent control group design. The experiment was conducted March to October 2022. The essay test of problem-solving and creativity was applied to measure students' problem-solving skills and creativity. Data collection in this study was carried out using Google Form, Google Classroom, Google meet, and WhatsApp. Data analysis using SPSS version 23 software. The analysis of covariate (ANCOVA) analysis results showed that HPBL affected problem-solving skills and student creativity with a value of p<0.005. The least significant difference (LSD) result was significantly different in improving problem-solving skills and creativity. The HPBL class gained the highest posttest score. Therefore, HPBL could be applicable to improve problem-solving skills and student creativity.